Survival Outcomes of Patients With Stage IB3 Cervical Cancer Who Undergo Abdominal Radical Hysterectomy Versus Radiochemotherapy - Li, Zhiqiang; Yang, Qing; Guo, Jianxin; Liang, Guoqiang; Duan, Hui; Wang, Shaoguang; Hao, Min; Liang, Wentong; Li, Donglin; Zhan, Xuemei; Xie, Qinghuang; Lang, Jinghe; et al. (Frontiers in Oncology, 2022)
Objective This study aimed to compare the survival outcomes among stage IB3 cervical cancer patients who undergo abdominal radical hysterectomy (ARH)+pelvic lymphadenectomy ± para-aortic lymph node dissection versus radiochemotherapy (R-CT). Methods Based on the large number of diagnoses and treatments for cervical cancer in the Chinese database, propensity score matching (PSM) was used to compare the 5-year overall survival (OS) and disease-free survival (DFS) rates of the ARH group and R-CT group. Results There were 590 patients with stage IB3 cervical cancer according to the FIGO 2018 staging system, with 470 patients in the ARH group and 120 patients in the R-CT group. The ARH and R-CT groups showed different 5-year OS and DFS rates in the total study population, and the 5-year OS and DFS rates in the R-CT group (n = 120) were lower than those in the ARH group (n = 470) (OS: 78.1% vs. 92.1%, p < 0.001; DFS: 71.6% vs. 90.3%, p < 0.001). R-CT was associated with a worse 5-year OS rate (hazard ratio [HR] = 3.401; 95% confidence interval [CI] = 1.875–6.167; p < 0.001) and DFS rate (HR = 3.440; 95% CI = 2.075–5.703; p < 0.001) by Cox multivariate analysis. After 1:3 PSM, the 5-year OS and DFS rates in the R-CT group (n = 108) were lower than those in the RH group (n = 280) (OS: 76.4% vs. 94.0%, p < 0.001; DFS: 69.3% vs. 92.6%, p < 0.001, respectively). R-CT was associated with a worse 5-year OS rate (HR = 4.071; 95% CI = 2.042–8.117; p < 0.001) and DFS rate (HR = 4.450; 95% CI = 2.441–8.113; p < 0.001) by Cox multivariate analysis. Conclusion Our study found that for FIGO 2018 stage IB3 cervical cancer patients, ARH resulted in better OS and DFS than R-CT.